Comparison of endoscopic submucosal dissection with laparoscopic-assisted colorectal surgery for early-stage colorectal cancer: a retrospective analysis - Kiriyama, S.; Saito, Y.; Yamamoto, S.; Soetikno, R.; Matsuda, T.; Nakajima, T.; Kuwano, H. (Endoscopy, 2012)
Background and study aims: Endoscopic submucosal dissection (ESD) is increasingly being used to resect early colorectal carcinoma, despite the technical difficulties associated with the procedure. Laparoscopic-assisted colorectal surgery (LAC) is an alternative to open surgery for colorectal cancers, and ESD was recently introduced as another alternative. In this study, we compared ESD with LAC as minimally invasive treatments for early colorectal cancer.Patients and methods: The study included 589 patients (297 patients with colorectal intramucosal or slightly submucosal invasive cancers undergoing ESD; 292 patients with T1 colorectal cancers undergoing LAC) who were treated at National Cancer Center Hospital in Tokyo, Japan, between January 1998 and September 2008. The clinical outcomes of ESD and LAC were evaluated retrospectively and compared on the basis of data that were originally collected prospectively.Results: In the ESD group, mean tumor size was 37 mm, mean procedure time was 106 minutes, and the en bloc and curative resection rates were 87 % and 80 %, respectively. There were 14 perforations (4.7 %) and 5 cases of postprocedure bleeding (1.7 %); all complications were successfully managed endoscopically except for one of the perforations, which required emergency surgery. In the LAC group, mean tumor size was 20 mm, mean operation time was 206 minutes, and complications included 31 wound infections, 2 pelvic abscesses, 3 anastomotic leakages, and 1 anastomotic bleed. Stomas were necessary in 93 % of the patients who underwent LAC for rectal cancers located below the peritoneal reflection.Conclusions: ESD was associated with a lower complication rate than LAC, with favorable en bloc and curative resection rates. The safety profile and possibility of curative treatment with colorectal ESD provide advantages for the treatment of early colorectal cancers with nul risk of lymph node metastasis.